The Work of Inclusion: An Ethnography of Grace, Sin, and Intellectual Disabilities. By Lorraine Cuddeback-Gedeon. New York: T&T Clark, 2023. xi + 183 pages. $29.95 (paper) - Vento, Johann M. (Horizons, 2024)
The Work of Inclusion: An Ethnography of Grace, Sin, and Intellectual Disabilities. By Lorraine Cuddeback-Gedeon. New York: T&T Clark, 2023. xi + 183 pages. $29.95 (paper).